Evaluating authorial ‘objectivity’ and ‘stancetaking’ in reporting the making of a new constitution in Zimbabwean newspapers - Sabao, Collen; Visser, Marianna (Taylor & Francis, 2016)
http://www.tandfonline.com.access.msu.ac.zw:2048/doi/abs/10.1080/02500167.2015.1011178